Improving Quality of Care Through Detection of Complexity Among Community‐Dwelling Older People Receiving District‐Nurse Support: ImPaCt Study Randomised Controlled Trial - Jennifer Boak; Tshepo Rasekaba; Irene Blackberry (Nursing Open, 2025)
ABSTRACT Aim To examine the effect of implementing the patient complexity instrument (PCI) in addition to usual‐care on complexity detection, clinical‐care time allocation and referrals to supportive services compared to usual‐assessment alone. Design A parallel‐group‐blocked pragmatic randomised controlled trial. Methods A mixed‐method study conducted within a regional Australian community nursing service. Randomisation occurred at the initial client assessment following referral acceptance for community nursing support. Older people aged 65 years and over (client participants), referred to the service from 1st of July 2020 to 30th of September 2020, were eligible for Commonwealth Home Support Programme funding. A convenience sample of community nurses conducting client assessments was recruited. The intervention group included usual assessment plus the PCI, and the control group was usual assessment alone. Chi‐square test independence compared complexity ratings (low, medium, high) between groups for the hypothesis that adding the PCI to usual assessment has no effect on nurses' complexity detection compared to usual assessment alone. Results Compared to usual‐assessment alone, adding the PCI did not change nurses' level detected complexity rating. However, for older people initially assessed with low levels of complexity, the PCI indicated a need for additional clinical‐care‐time. The nurses' contribution to process evaluation showed that the PCI was useful in providing prompts for aspects to consider during their assessment. Conclusion The addition of PCI to nurses' usual assessment did not improve levels of complexity ratings. However, the PCI enhanced complexity detection by pinpointing areas of care requiring referrals for additional care and extra time required. The ImPaCt trial demonstrated the PCI as a useful tool for enhancing care for older people receiving nursing support in the community. The PCI is a beneficial guidance resource for those new to the Community Nursing role caring for older people. Reporting Method The study adhered to the updated guidelines for reporting parallel group randomised trials. Reporting was conducted according to the CONSORT checklist. Patient or Public Contribution This study was focused on the nurses' perspective of client complexity and how this complexity is detected. During the protocol development phase, a presentation about the study was made to a consumer group (older people) from the lead researcher's workplace. This presentation was well received, with five consumers in attendance. The protocol was also presented to the Board of the lead researcher's workplace, which was a large regional public health service. Four board members were in attendance and showed positive interest. Implications for the Profession and Patient Care This study underscores the merit of incorporating a care complexity assessment tool into community nursing care for older people, amplifying decision‐making regarding patient complexity. Future studies should explore clients' perspectives, the PCI's effect on and implications for hospital (re)admissions and longevity at home. Trial Registration: The trial was registered with the Australian and New Zealand Clinical Trials Registry (blinded for review)